Role Of Cognitive Emotion Regulation Strategies (CERS) And Mental Health Among School Going Students - Pooja, Devi; Dr.Shabana Anjumm (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Adolescent mental health is a growing concern worldwide, with increasing rates of depression, anxiety, and other psychological disorders among this age group. Comprehensive Education on Resilience Skills (CERS) programs have emerged as a potential intervention to address these challenges. Adolescent mental health disorders are a significant concern, relatively prevalent, and amenable to treatment or intervention. Obstetrician gynaecologists who see adolescent patients are highly likely to see adolescents and young women with one or more mental health disorders. Some of these disorders may interfere with a patient's ability to comprehend or articulate her health concerns and appropriately adhere to recommended treatment. Some disorders or their treatments will affect the hypothalamic-pituitary-gonadal axis, causing anovulatory cycles and numerous menstrual disturbances. Adolescents with psychiatric disorders may take psychopharmacologic agents to induce menstrual dysfunction and galactorrhea. Adolescents with mental illness often engage in acting-out behaviour or substance use, which increases their risk of hazardous sexual behaviour that may result in pregnancy or sexually transmitted infections. This abstract summarizes the findings of a systematic review and meta-analysis that investigates the effect of CERS on adolescent mental health outcomes. The present study has the following objectives. To evaluate the Impact of Comprehensive Emotional Resilience Support (CERS) programmes on adolescents' mental health. To Examine the relationship between CERS interventions and adolescents' psychological health. The questionnaires were administered equally to 100 adolescents, 50 males and 50 females. Excel was used during the selection procedure to evaluate the Impact of CERS on adolescents' mental health. The investigation provided helpful and useful results and valuable suggestions for future research. After getting all the required data, the study examined the Impact of CERS on the mental health of both male and female adolescents.